Pemberdayaan UMKM sebagai Strategi Pemerintah untuk Mengurangi Kemiskinan di Indonesia Tahun 2020–2023 - Ariani, Azrene Dwi; Cahyono, Diniardy Zouly Indra; Azizah, Rhobatin Nur (Journal of Economics and Social Sciences (JESS), 2024)
Introduction/Main Objectives: Poverty remains a significant challenge for Indonesia's economic development, further exacerbated by the COVID-19 pandemic, making the empowerment of Micro, Small, and Medium Enterprises (MSMEs) a key strategy for sustainable solutions. This study aims to analyze government strategies for poverty alleviation in Indonesia through MSME empowerment during the period 2020–2023. Research Methods: The research employs a qualitative approach with a literature review, encompassing articles, scientific journals, books, and official government reports, to identify policies, programs, and challenges encountered. Finding/Results: The findings reveal that (1) financial assistance and subsidies for MSMEs helped sustain businesses during the pandemic; (2) MSME digitalization programs, including e-commerce training and digital platform provision, enhanced the competitiveness of local products; and (3) entrepreneurial training and market access expansion improved MSME capacities, although implementation remains uneven across Indonesia. Key challenges include limited digital literacy, inadequate infrastructure in remote areas, and weak oversight of aid distribution. Conclusion: This study concludes that MSME empowerment holds significant potential for poverty reduction if supported by sustainable policies, infrastructure strengthening, cross-sector collaboration, and continuous literacy and mentoring initiatives.